A Compact Instrument for Temperature-Programming-Assisted Capillary–Nanoliquid Chromatography - Lincon Coutinho Marins; Alessandra Maffei Monteiro; Vivane Lopes Leal; Deyber Arley Vargas Medina; Edwin Martin Cardenas; Fernando Mauro Lanças (Separations)
The miniaturization of liquid chromatography (LC) columns to capillary and nanoscales allows temperature programming to be an effective alternative to solvent gradients for modulating eluotropic strength. This approach simplifies instrument design and operation, as a single pump can suffice to achieve efficient separations. This study presents the development and application of a compact, lab-built high-pressure system for temperature-programmed capillary and nanoLC separations. The instrument includes a high-pressure capillary–nanoflow syringe pump, a time-based nanoliter injection system, a programmable capillary column oven for controlled temperature gradients, and a UV-Vis detection system with a custom nanoliter-scale detection cell. Each system component was designed and built in-house, with rigorous calibration to ensure accuracy and operational reliability. Experimental data confirm the system’s capability to deliver precise, reproducible temperature, and flow rates. Functionality was validated through temperature-programmed separations on packed and open tubular capillary columns. The results demonstrated that the developed instrument offers enhanced separation efficiency and reduced analysis time compared to isothermal methods, underscoring its potential for advanced applications in miniaturized liquid chromatography.